Neural and behavioral correlates of human pain avoidance in participants with and without episodic migraine: research paper - Gandhi, Wiebke; de Vos, Cecile C.; Becker, Susanne; Hoge, Richard D.; Hoeppli, Marie-Eve; Schweinhardt, Petra (Pain, 2022)
The innate motivation to avoid pain can be disrupted when individuals experience uncontrollable stress, such as pain. This can lead to maladaptive behaviors, including passivity, and negative affect. Despite its importance, motivational aspects of pain avoidance are understudied in humans and their neural mechanisms vastly unknown. Rodent models suggest an important role of the periaqueductal gray, but it is unknown whether it subserves a similar role in humans. Furthermore, it is unclear whether pain avoidance is associated with individual differences in pain coping. Using functional magnetic resonance imaging, networks underlying pain avoidance behavior were examined in 32 participants with and without episodic migraine. Pain avoidance behavior was assessed using an adaptation of the incentive delay task. In each trial of the task, participants tried to avoid a painful stimulus and receive a nonpainful one instead while the difficulty to succeed varied across trials (3 difficulty levels: safe, easy, and difficult). After unsuccessful pain avoidance on the preceding trial, participants showed reduced pain avoidance behavior, especially in the difficult condition. This reduction in behavior was associated with higher helplessness scores only in participants with migraine. Higher helplessness in participants with migraine was further correlated with a stronger decrease in activation of cortical areas associated with motor behavior, attention, and memory after unsuccessful pain avoidance. Of these areas, specifically posterior parietal cortex activation predicted individual's pain avoidance behavior on the next trial. The results link individual pain coping capacity to patterns of neural activation associated with altered pain avoidance in patients with migraine.